Gaultheria marronina sp. nov. (Ericaceae) from Sichuan, China. (12th May 2016) - Fritsch, Peter W.; Lu, Lu; Xu, Bo; Wang, Hong; Li, De‐Zhu
Abstract : Gaultheria marronina, a new species from the Hengduan Mountain chain of western Sichuan Province, China, is described and illustrated. This species is similar to G. bryoides P. W. Fritsch & L. H. Zhou from the Gaoligong Mountains in its white fleshy calyx with a maroon capsule but differs in its stem setae 0.34–0.50 mm long, petioles 0.4–0.6 mm long, leaf blades 5.1–6.2 × 2.1–3.1 mm, overwintering flower bud pedicels 0.6–0.8 mm long, calyx lobes 2.2–3.0 mm long, and usually slightly open fruiting calyx, among other characters. The species is known only from two widely separated unprotected populations and is categorized as endangered.